Assessing the influence of farmers’ socio-economic orientation on the adoption of recommended soil fertility management practices - Kwame Agyei Frimpong; Ransford Opoku Darko; Selorm Akaba; Isaac Boateng; Agnes Naa Abeley Abbey (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study examines how the socio-economic orientation of smallholder farmers influences their soil fertility management decisions. Smallholder farmers, numbering 100 from the Sekyere South District in the semi-deciduous forest and the Komenda-Edina-Eguafo-Abirem (KEEA) District in the coastal savannah agroecological zones of Ghana, respectively, were involved in the study, which adopted the mixed-methods approach to assess their knowledge and awareness of the 4R Nutrient Stewardship (4RNS) and Integrated Soil Fertility Management (ISFM) strategies. A semi-structured survey instrument was used to explore how socio-economic factors such as level of education, age, land tenure, and access to technical and financial support influence the farmers’ soil fertility management decisions. The results revealed that 57.9% of farmers were aware of the ISFM, while 43.2% were aware of the 4RNS, indicating an information deficit. Nonetheless, about 77.6% of the farmers expressed the willingness to implement both soil fertility management approaches, contingent upon receiving sufficient technical training and financial assistance. The results confirmed that inadequate financial resources, limited access to technical expertise, educational attainment, and land tenure insecurity constrained, especially youthful and female farmers, from adopting recommended soil fertility management practices. Thus, farmers with higher levels of education were more likely to implement recommended soil fertility practices, while those without stable land tenure were less motivated to adopt the recommended soil fertility management strategies. The study demonstrated that the socio-economic orientation of smallholder farmers greatly influenced their adoption and investments in soil fertility management practices. Int. J. Agril. Res. Innov. Tech. 15(2): 107-126, Dec 2025